2016
DOI: 10.1080/13510002.2016.1215120
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cysteine 457 in plakoglobin modulates the proliferation and migration of colorectal cancer cells by altering binding to E-cadherin/catenins

Abstract: Pg appears to be redox-sensitive in cancer, and the C457 modification may impair cell migration and proliferation by affecting its interaction with the E-cadherin/catenin axis. Our findings suggest that redox-sensitive cysteines of Pg may be the targets for CRC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The current results highlight that Sirt7 not only increased N-cadherin expression, but also regulated E-cadherin transcription in an E-box-dependent manner. Notably, although E-cadherin is traditionally considered as a suppressor of cell invasion, the present study observed the inhibitory function of E-cadherin on the cell proliferation, similarly to the findings of Kim et al ( 31 ) and Ji et al ( 32 ) reported in CRC and pancreatic cancer. Although the higher Sirt7 group had a worse overall survival rate, the deaths of the lower Sirt7 group may be due to the complicated tumor metastatic mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…The current results highlight that Sirt7 not only increased N-cadherin expression, but also regulated E-cadherin transcription in an E-box-dependent manner. Notably, although E-cadherin is traditionally considered as a suppressor of cell invasion, the present study observed the inhibitory function of E-cadherin on the cell proliferation, similarly to the findings of Kim et al ( 31 ) and Ji et al ( 32 ) reported in CRC and pancreatic cancer. Although the higher Sirt7 group had a worse overall survival rate, the deaths of the lower Sirt7 group may be due to the complicated tumor metastatic mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, γ-catenin, known as junction plakoglobin (JUP), interacts with the cytoplasmic domain of cadherins (McEwen et al, 2014 ). In colorectal cancer cells, the C457 modification of γ-catenin results in impaired migration and proliferation of cells by affecting the “cadherin switch” (Conacci-Sorrell et al, 2002 ; Kim et al, 2017 ). However, it is unclear whether the catenin/cadherin complex influences the progression of EMT in lipid nephrotoxicity and therefore warrants confirmation.…”
Section: Introductionmentioning
confidence: 99%